1998
DOI: 10.1006/brcg.1997.0969
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Random Generation

Abstract: This study investigated the effects of age on a random generation task. In Experiment 1, young and elderly subjects were asked to generate random strings of letters at 1-, 2-, and 4-s rates. The elderly subjects produced more alphabetical stereotype responses than young subjects, even in the slowest rate condition. Furthermore, as faster rates were imposed, elderly subjects could no longer maintain the pace and missed responses. In Experiment 2, subjects were required to generate letters at the same time that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 25 publications
5
25
1
1
Order By: Relevance
“…However, it would appear that the influence was limited to psychomotor speed, as only TMT-A performance was significantly predicted by gender. In addition, our results indicated that TMT-B was influenced by a small but significant effect of education, which is consistent with the more general effect of this variable on executive function (Daigneault & Braun, 1993;Fisk & Warr, 1996;Keys & White, 2000;Schretlen et al, 2000;Van der Linden, Beerten, & Pesenti, 1998;West, 2001). The influence of education was of particular interest due to the relative absence of education-adjusted normative data in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…However, it would appear that the influence was limited to psychomotor speed, as only TMT-A performance was significantly predicted by gender. In addition, our results indicated that TMT-B was influenced by a small but significant effect of education, which is consistent with the more general effect of this variable on executive function (Daigneault & Braun, 1993;Fisk & Warr, 1996;Keys & White, 2000;Schretlen et al, 2000;Van der Linden, Beerten, & Pesenti, 1998;West, 2001). The influence of education was of particular interest due to the relative absence of education-adjusted normative data in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Additional support comes from recent studies examining developmental change in random number generation. When adults are required to generate random numbers, they exhibit a strong tendency to avoid repetitions (Kareev, 1992;van der Linden, Beerten, & Pesenti, 1998; but see Nickerson, 2002). The tendency to favor alternations in random number generation is less pronounced in children (Towse & McLachlan, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The participants were explicitly instructed to take their time in order to answer, and no particular response time window was imposed. It was pointed out that the number sequence should be wholly jumbled and should not consist of systematic ascending, descending, or somehow ordered sequence (for similar instructions, see Van der Linden et al 1998). On average, a trial lasted about 2500 ms.…”
Section: Methodsmentioning
confidence: 99%